Examining the efficacy of a digital version of the Self-Administered Interview - Fiona Gabbert (Elsevier, 2022)
Objectives: The Self-Administered Interview (SAI©) is an investigative tool designed to facilitate the reporting of comprehensive initial statements by witnesses. Given increasing use of technology to communicate, many witnesses may prefer to provide investigators with accounts of what they have seen using online or mobile reporting platforms. Research shows that the SAI© elicits more accurate information from witnesses than other reporting formats. To date, however, the SAI© has only been tested in a paper-based format. The aim of the current research was to examine whether the benefits of the SAI© for witness reporting extend to digital reporting formats. Method: In two experiments, we examined whether completing the SAI© on a computer or mobile device (as opposed to using a paper-based format) had any effect on the quantity or quality of information reported by mock witnesses. We also assessed whether the format of the initial report had any impact on performance in a delayed recall test. Hypotheses: Based on available research on use of technology, we expected that witness accounts would be shorter when provided via mobile devices than via other formats. Drawing on past research outlined in the Introduction, we predicted that less detailed initial accounts would affect the quality of subsequent accounts. Results: We found no differences between computer, mobile, or paper-based formats with respect to the quantity or quality of information reported in the SAI© or content of follow-up reports collected one-week later. Conclusion: The findings suggest that administering the SAI© in online or mobile formats is unlikely to be detrimental to witness reporting. Given the time and resource costs associated with paper forms, as well as the additional functionality that digital presentation may afford, a digital SAI© may prove to be a useful investigative tool.